Calibration of Radiation Portal Monitors for Characterization of Historic Low-level Radioactive Waste. Issue 3 (September 2018) - Cole, David; Martin-Burtart, Nicolas
Abstract : Abstract: Radiation portal monitors are large-volume radiation detectors typically positioned along roadways, railways, and pedestrian portals. They are typically used for the detection of radioactive material where no such material is expected. Applications include monitoring vehicles and personnel exiting nuclear facilities, at the entrance to steel and scrap metal facilities, and at international borders. As part of the Port Hope Area Initiative, the Port Granby Project involves the relocation of approximately 450, 000 m 3 of historic low-level radioactive waste, located at an existing site on the shoreline of Lake Ontario in Southeast Clarington, to a new, engineered aboveground mound. Ongoing maintenance and monitoring will continue for hundreds of years after the facility is capped and closed. The waste is transported from its current location about 700 m to the new facility using trucks. Each truck passes through a radiation portal monitor when travelling between the waste location and waste storage facility (both directions; empty and full). The radiation portal monitors have been calibrated to provide an estimate of the total radioactivity being deposited into the new waste facility. This paper describes the methodology and results of the calibration.